Criteria for assessing endogenous intoxication in patients with multiple peritonitis - Boyko, Valeriy V.; Likhman, Viktor M.; Shevchenko, Oleksandr M.; Merculov, Andriy O.; Ponomarova, Kateryna V.; Bilodid, Yevhenii O.; Tkach, Serhiy V. (ALUNA Publishing House, 2022)
To determine the diagnostic significance of the level of malondialdehyde (MDA) in various biological media for RP for assessing and predicting the course of the disease. Materials and methods: Our study included The work was based on the results of surgical treatment of 60 patients with RP: according to MPI I - in 17 (28.3%), MPI II - in 23 (38.4%) and MPI III - in 20 (33.3%) patients. Surgical intervention for RP was aimed at sanitation and drainage of the abdominal cavity. The control group included 15 practically healthy people, whose blood and urine biochemical parameters served as the norm. According to the clinical course of the disease, the patients were divided depend on admission, The secondary product of lipid peroxidation - MDA was studied in blood serum, peritoneal exudate and urine in patients with RP, depending on the severity of the pathological process according to the Mannheim peritoneal index (MPI) - I severity (I), II severity (II), III severity (III). The work was based on the results of surgical treatment of 60 patients with RP: according to MPI I - in 17 (28.3%), MPI II - in 23 (38.4%) and MPI III - in 20 (33.3%) patients. Results: Analyses of results showed that the average value of MDA in various biomedicals of recovered (n = 18) and subsequently died (n = 5) patients with MPI II are given in Table. 2. As can be seen from the presented data, the average value of MDA in blood serum and peritoneal exudate in patients with a lethal outcome is significantly higher than in those who have recovered. This fact indicates a more pronounced endogenous intoxication in patients who died from RP. Conclusions: The content of MDA in the blood serum before surgery in patients with a lethal outcome was 190% (p <0.001). The level of MDA in urine in patients according to MPI II who subsequently died before surgery was 110% (p <0.001), and in those who recovered by 300% (p <0.001) it was higher than the norm. exudate taken during the operation averaged 4.14 ± 0.33 nmol / ml, then in the recovered - 2.89 ± 0.08 nmol / ml. A high level of MDA in the blood serum, peritoneal exudate with a decrease in the elimination of MDA in the urine in the postoperative period are prognostically unfavorable signs in patients, indicating the continuation of endogenous intoxication and a possible death.
Keywords: endogenous intoxication; generalized peritonitis; malondialdehyde (MDA); inflammation